Optical fiber pressure sensor based on full polylactic acid
Through the design of all polylactic acid-based materials and structural, the non-degradability and biocompatibility problems of traditional fiber optic pressure sensors are solved, and the stability and precise measurement of the degradable fiber optic pressure sensors are achieved, reducing medical risks.
Patent Information
- Application Number
- CN202510672090.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-08-22
AI Technical Summary
Traditional fiber optic pressure sensors use non-degradable materials, which require secondary surgery to remove after implantation, increasing medical risks. The material does not match the mechanical properties of biotissue, which is prone to breaking, causing chronic inflammatory reactions.
The base, pressure-sensitive diaphragm and optical fiber made of all polylactic acid (PLA)-based materials are used to achieve degradability and synchronous degradation of each component through blending modification and structural design. Nanocellulose is used to enhance mechanical strength, and polylactic acid (PLA)/polycaprolactone (PCL) multi-layer reflective film replaces metal coating to regulate the degradation rate.
It realizes complete degradation of the sensor within a few months after implantation, without secondary surgery, reduces medical risks, excellent mechanical properties, non-toxicity of the degradation product, high sensor stability and measurement accuracy, and good degradation synchronization.
Smart Images

Figure CN120521776A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sensors, and in particular to an optical fiber pressure sensor based on polylactic acid. Background Art
[0002] With the rapid development of implantable medical devices, fiber optic pressure sensors, thanks to their tiny size and excellent biocompatibility, can be implanted in the human body to provide real-time, accurate measurement of physiological parameters such as blood pressure, intracranial pressure, and pulmonary pressure, providing important evidence for disease diagnosis and treatment. Traditional fiber optic pressure sensors use quartz or non-degradable plastic optical fibers, requiring secondary surgical removal after implantation, increasing medical risks. Non-degradable materials can also trigger chronic inflammatory reactions. Quartz optical fibers are also prone to breakage and have issues matching the mechanical properties of biological tissue. Summary of the Invention
[0003] The purpose of the present invention is to provide a fully degradable optical fiber pressure sensor based on polylactic acid.
[0004] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: an optical fiber pressure sensor based on polylactic acid, comprising a base, a pressure-sensitive diaphragm and an optical fiber, The base is a blend of polylactic acid (PLA) and nanocellulose; The pressure-sensitive film is a blend of polylactic acid (PLA), nanocellulose, and hydroxyapatite; The optical fiber includes a core layer and a cladding layer. The core layer material is high-purity polylactic acid (PLA), and the cladding material is a blend of polylactic acid (PLA) and polyhydroxyalkanoate (PHA).
[0005] Furthermore, in the pressure-sensitive film, the mass ratio of polylactic acid (PLA), nanocellulose and hydroxyapatite is (70-88): (8-22): (2-7).
[0006] Furthermore, in the optical fiber cladding, the mass ratio of polylactic acid (PLA) to polyhydroxyalkanoate (PHA) is (80-95): (5-20).
[0007] Furthermore, a concave cavity is provided on the base, and a pressure-sensitive film cover is provided at the opening of the concave cavity to form an FP cavity. A reflective film is provided at the two end faces of the FP cavity, and the reflective film is a multilayer polylactic acid (PLA) / polycaprolactone (PCL) film.
[0008] Furthermore, multiple layers of polylactic acid (PLA) layers and polycaprolactone (PCL) layers are arranged alternately, and the innermost layer is the polylactic acid (PLA) layer.
[0009] Furthermore, the reflective film has 5 to 10 layers in total and a thickness of 0.5 to 1.5 μm.
[0010] Furthermore, the base includes a first substrate and a second substrate, the first substrate is provided with a first through hole, the first through hole and the surface of the second substrate and the surface of the pressure-sensitive membrane together enclose an FP cavity, and the reflective film is provided on the surface of the pressure-sensitive membrane and the surface of the second substrate in the FP cavity.
[0011] Furthermore, an optical fiber sleeve is provided on the second substrate, and the inner cavity of the optical fiber sleeve and the surface of the second substrate enclose an optical fiber installation portion. The FP cavity and the optical fiber installation portion are coaxial and spaced apart in the axial direction of the optical fiber.
[0012] Furthermore, the mass ratio of polylactic acid (PLA) and nanocellulose in the base is (95-97): (3-5), and the optical fiber sleeve is pure polylactic acid (PLA).
[0013] Furthermore, the outer surface of the sensor is sprayed with a PLA protective layer with a thickness of 3 to 6 μm to maintain degradation synchronicity.
[0014] The above scheme has at least the following beneficial effects: The sensor's base, perforated plate, pressure-sensitive membrane, and optical fiber are all made of degradable polylactic acid (PLA). The sensor can be completely degraded into CO2 and H2O within a few months after implantation, avoiding secondary surgery. Nanocellulose-reinforced polylactic acid (PLA) is used as a pressure-sensitive membrane to improve mechanical strength and deformation linearity; core-cladding structure polylactic acid (PLA) optical fiber achieves light transmission through refractive index regulation; polylactic acid (PLA)-based multilayer reflective film is used instead of metal coating to achieve a degradable Fabry-Perot cavity reflective interface; The performance and degradation balance is achieved through blending and modification of each component material, and the degradation of each component is synchronized, thus ensuring the stability of the sensor; The multilayer reflective film optimizes the alternating coating of polylactic acid (PLA) and polycaprolactone (PCL), and achieves synchronous degradation with the main material through complementary material degradation characteristics; Optical fiber core-cladding material matching: The core layer uses pure polylactic acid (PLA), and the cladding uses a polylactic acid-polyhydroxyalkanoate (PHA) blend (PLA-PHA). This adjusts the degradation rates of the core and cladding to be close to each other to avoid breakage; Degradation product diffusion channel: The through-hole design on the second substrate and the optical fiber sleeve through-hole promotes the diffusion of acidic products and avoids local degradation differences.
[0015] Structural size adaptation degradation model: The thickness design of the diaphragm, base, etc. is combined with degradation dynamics simulation, and the volume / surface area ratio is matched with the degradation rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Schematic diagram of the overall structure of the optical fiber pressure sensor; Figure 2 for Figure 1 Schematic diagram of the middle part structure; Figure 3 is the sensor reflection spectrum; Figure 4 This is the linear relationship diagram between wavelength drift and force change / pressure response curve. DETAILED DESCRIPTION
[0017] The operating principle of a Fabry-Perot cavity fiber pressure sensor is as follows: a stable light source emits a beam, which is transmitted via optical fiber to the sensor's FP cavity. The beam undergoes multiple reflections within the FP cavity, generating interference. The resulting interference pattern depends on the cavity length. External pressure is applied to the elastic diaphragm, causing it to deform, thereby changing the length of the FP cavity. As the cavity length changes, the characteristics of the interference pattern also change, such as the phase shift of the interference fringes. A spectrum analyzer or other suitable detection device is used to capture and interpret the phase shift of the interference pattern, and after signal processing, the actual pressure value is obtained. Ultimately, the sensor outputs the detected pressure information as a digital or analog signal for user reading or further processing.
[0018] Next, combine Figure 1 、 Figure 2 The present invention is discussed in detail.
[0019] An optical fiber pressure sensor based on polylactic acid includes a base 10, a pressure-sensitive membrane 20 and an optical fiber 30. Base 10 is a blend of polylactic acid (PLA) and nanocellulose. PLA is a synthetic polymer material, a linear thermoplastic aliphatic polyester. It is synthesized using starch extracted from plants such as corn, wheat, cassava, rye, rice, sugarcane, or sugar beets as its starting material. High-purity PLA is synthesized through a complex series of processing steps. PLA products can be completely decomposed into carbon dioxide and water by the action of water, microorganisms, acids, and alkalis, exhibiting excellent biocompatibility and biodegradability. Cellulose nanomaterials are emerging nanomaterials. They are produced from renewable raw materials at a relatively low cost, are biodegradable and biocompatible, and have strong water absorption capacity, while also possessing sufficient mechanical strength and stiffness. Nanocellulose is used to reinforce PLA, improving the mechanical strength of the base, ensuring it meets the performance requirements of a sensor base.
[0020] The pressure-sensitive film 20 is a blend of polylactic acid (PLA), nanocellulose and hydroxyapatite. Polylactic acid (PLA) is highly rigid but brittle and cannot be used alone as a pressure-sensitive film. It needs to be modified to improve its toughness. Nanohydrogen-based apatite (nHA) generated by the reaction of nanocellulose and hydroxyapatite can fill the pores of polylactic acid (PLA), improve the compressive / flexural strength, and improve the mechanical strength and deformation linearity.
[0021] Traditional quartz optical fibers are prone to breakage, lack the mechanical properties of biological tissue, and are incompatible with decomposition, potentially triggering chronic inflammatory reactions. The optical fiber 30 of the present invention comprises a core layer and a cladding layer. The core layer is made of high-purity polylactic acid (PLA), while the cladding is a blend of PLA and polyhydroxyalkanoate (PHA). PLA and PLA-PHA blends exhibit excellent compatibility, reducing interfacial defects during melt coextrusion. The addition of PHA enhances the cladding's flexibility and impact resistance, adapting to the bending and stretching requirements of the optical fiber.
[0022] In the present invention, the base 10, the pressure-sensitive membrane 20 and the optical fiber 30 are all made of polylactic acid (PLA)-based materials. All components are degradable and do not require secondary surgery to remove after implantation into the human body, effectively reducing medical risks.
[0023] For implantable sensors, it is not enough to just satisfy the requirement that each component is degradable. What is more important is the synchronization of degradation of each component, because the synchronization of degradation of each component is the key to ensuring the stability and measurement accuracy of the sensor, and its influencing factors are closely related to material properties and structural design.
[0024] As a preferred embodiment of the present invention, the mass ratio of polylactic acid (PLA), nanocellulose, and hydroxyapatite in the pressure-sensitive film 20 is (70-88): (8-22): (2-7). The polylactic acid (PLA) is modified by nano-hydroxyapatite (nHA), thereby improving the mechanical strength and deformation linearity of the pressure-sensitive film 20. See Table 1: Table 1 Through material modification (such as compatibilizers, surface treatment), process optimization (directional stretching, solvent gradient volatilization) and functional compensation (refractive index matching agent, hydrolysis catalyst), the mass ratio range can be expanded to (70-88): (8-22): (2-7), while maintaining the core indicators of transmittance >90%, sensitivity ≥0.1 nm / kPa, and degradation synchronization difference <15%.
[0025] It can be seen from Table 1 that the pressure-sensitive film 20 made of this material composition has both high mechanical strength and pressure-sensing performance; the tensile strength, elastic modulus and sensitivity are all at high values, suitable for high-resolution sensors; and it also has good biodegradation synchronization and stability.
[0026] Diaphragm pressure sensing principle: According to the principles of elastic mechanics, when external pressure acts evenly on the surface of a circular diaphragm with uniform thickness and tight edges, the expression for the deformation of each point on the diaphragm is:
[0027] In the above formula, P Indicates the pressure on the diaphragm. R 0 represents the diaphragm radius, r represents the radius of any point on the diaphragm, D=Et 3 / 12(1-ν 2 ) is the bending stiffness of the diaphragm, where t is the thickness of the diaphragm, E and ν They represent the Young's modulus and Poisson's ratio of the diaphragm material respectively. It can be seen that the deformation of the diaphragm is proportional to the pressure on the diaphragm. r = 0, that is, the change in the center position of the diaphragm can be expressed as:
[0028] Fabry-Perot cavity center length L It can be expressed as:
[0029] In the above formula, h is the depth of the Fabry-Perot cavity. In summary, the sensitivity expression can be obtained as follows:
[0030] The above formula shows that pressure sensitivity is related to the mechanical properties of the sensor's diaphragm material and the sensor's structural parameters. It is directly proportional to the fourth power of the diaphragm radius and inversely proportional to the cube of the diaphragm thickness. Therefore, the larger the diaphragm radius and the smaller the thickness, the higher the diaphragm's pressure sensitivity. It's important to note that to ensure good linearity in the change of diaphragm deformation with pressure, the diaphragm deformation should be controlled within 20% of the diaphragm thickness.
[0031] Similarly, in the cladding of optical fiber 30, the mass ratio of polylactic acid (PLA) to polyhydroxyalkanoate (PLA) is (80-95): (5-20), meeting the requirements of the optical fiber drawing process. Light transmission is achieved through refractive index control. Through reasonable component selection, the degradation rates of the core and cladding are controlled to be close to each other, avoiding breakage of the finished optical fiber. The characteristics of the finished optical fiber are shown in Table 2: Table 2 performance Elongation (%) Refractive index (1550nm) Waveguide loss (dB / km) Degradation rate matching difference (%) parameter 12 ± 1 1.45 <0.1 <10% As can be seen from Table 2: the optical fiber has a stretchability of up to 12%, and has flexible properties; the refractive index of 1.45 meets the sensor waveguide requirements; the degradation rate differs from the pressure-sensitive membrane and the base by less than 10%, and has good stability; the optical loss is extremely low, making it suitable for high-sensitivity detection in the body.
[0032] A concave cavity is formed on the base 10, and a pressure-sensitive film 20 covers the opening of the cavity, forming the FP cavity. Reflective films 40 are provided on both end faces of the FP cavity. These reflective films are composed of a multilayer polylactic acid (PLA) / polycaprolactone (PCL) film. Using a PLA-based multilayer reflective film instead of a metal coating creates a degradable Fabry-Perot cavity reflective interface. Specifically, the high ductility of PCL (elongation at break >300%) compensates for the brittleness of PLA, making the multilayer film more suitable for flexible applications. Hydrogen bonds or van der Waals forces formed at the interface enhance interlayer adhesion and prevent delamination. PLA degrades slowly through hydrolysis, while PCL degrades rapidly through esterase catalysis. The multilayer structure allows for a step-by-step degradation process, allowing for precise control of degradation rates and achieving synchronized degradation across the entire sensor.
[0033] Multiple layers of polylactic acid (PLA) and polycaprolactone (PCL) are arranged alternately. This alternating arrangement achieves a balance of strength and toughness. The PCL layer acts as a plastic deformation layer, absorbing impact energy and reducing stress concentration in the PLA layer, thereby improving impact resistance. The alternating arrangement also achieves a step-by-step degradation pattern, avoiding structural failure caused by rapid degradation of a single material. Since both the pressure-sensitive diaphragm 20 and the base 10 are made of a PLA-based material, the innermost layer is the PLA layer. This innermost layer refers to the layer directly attached to the substrate. This provides a higher bond strength between similar materials, ensuring a reliable connection between the reflective film 40 and the end face of the FP cavity.
[0034] Taking into account the synergy with the degradation rate of other components, the reflective film 40 is provided with 5 to 10 layers with a thickness of 0.5 to 1.5 μm to meet the requirements of mechanical and degradation balance.
[0035] The base 10 comprises a first substrate 11 and a second substrate 12. A first through-hole 111 is provided on the first substrate 11. The first through-hole 111, along with the surface of the second substrate 12 and the surface of the pressure-sensitive membrane 20, encloses a FP cavity. A reflective film 40 is disposed on the surface of the pressure-sensitive membrane 20 and the surface of the second substrate 12 within the FP cavity. The base 10 is assembled as a single unit using a multi-layered substrate bonding process. The first substrate 11, where the first through-hole 111 is to be provided, is provided as a separate layer, into which the first through-hole 111 is machined. Since the first through-hole 111 is continuous, surface unevenness caused by wet etching or ion etching is avoided, thereby ensuring high flatness of the reflective film on the FP cavity end face and high sensor accuracy. This also ensures high sensor consistency, ensuring stable performance across the entire sensor batch.
[0036] In order to fix the optical fiber 30, an optical fiber sleeve 50 is provided on the second substrate 12. The inner cavity of the optical fiber sleeve 50 and the surface of the second substrate 12 form an optical fiber mounting portion. The FP cavity and the optical fiber mounting portion are coaxial and spaced apart in the axial direction of the optical fiber 30. The end of the optical fiber 30 is against the base 50. The surface of the base 50 is highly flat, which reduces the deviation of the optical signal during reception and reduces the impact of signal loss.
[0037] Preferably, the mass ratio of polylactic acid (PLA) to nanocellulose in base 10 is (95-97): (3-5). The nanocellulose forms a good interfacial bond with the PLA matrix, enhancing stress transfer through physical crosslinking or chemical bonding, while also promoting PLA crystallization and increasing crystallinity. When the nanocellulose content is 5%, the composite material reaches optimal tensile strength and elongation at break. The optical fiber sleeve 50 is made of pure polylactic acid (PLA), which has at least the following beneficial effects: (1) Optimized transmittance: the transmittance of the pure PLA sleeve at a wavelength of 1550 nm is >92%; (2) Degradation rate matching: the optical fiber sleeve 50 has a thin-walled structure, and the degradation rate of pure PLA (24 months) can be accelerated to synchronize with the base 10 (difference <10%) by reducing the molecular weight (Mw=50kDa), without relying on additives; (3) Interface bonding reliability: the difference in thermal expansion coefficient between the pure PLA sleeve and the PLA-PHA cladding optical fiber (Δα=1.2×10⁻ 5 / ℃) is significantly smaller than that of PLA containing nanocellulose (Δα=2.5×10⁻ 5 / ℃), the interfacial stress is reduced by 70% during low temperature bonding, avoiding the generation of microcracks; (4) Process compatibility: pure PLA has no interference from the light absorption of nanoparticles during UV curing, and the curing efficiency is increased by 40%.
[0038] The outer surface of the sensor is sprayed with a PLA protective layer with a thickness of 3 to 6 μm to maintain degradation synchronization.
[0039] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, five groups of examples under the same preparation process conditions are given below. The component formulas involved in Examples 1 to 5 are shown in Table 3: Table 3
[0040] Fiber optic pressure sensors were prepared and assembled according to the components given in Examples 1-5. The performance of each group of sensors is shown in Table 4: Table 4 performance Example 1 Example 2 Example 3 Example 4 Example 5 Light transmittance (%) 92 91 90 88 85 Interference fringe contrast (%) 85 82 78 75 70 Pressure sensitive diaphragm sensitivity (nm / kPa) 0.15 0.13 0.10 0.08 0.04 Sensor sensitivity (kPa⁻¹) 0.1 0.09 0.08 0.07 0.03 Difference in degradation rate of each component (%) 15 18 20 25 >30 Total degradation cycle (months) 8 9 10 12 >18 Biocompatibility Better Better Better Better Better in: Sensitivity test method: Use an air pressure chamber to apply a pressure of 0 to 10 kPa, and the spectrometer detects the wavelength shift Δλ. Calculate the sensitivity: k = PΔλ (target value ≥ 0.08 nm / kPa) Degradation rate verification method: The fiber optic pressure sensor was immersed in PBS buffer (37°C, pH=7.4) and the weight loss and tensile strength attenuation were measured weekly until complete degradation.
[0041] Biocompatibility test method: Cytotoxicity test (MTT method) and hemolysis rate test (target value <5%) were performed according to ISO 10993 standard.
[0042] As can be seen from Tables 1 to 4, the performance of the optical fiber pressure sensor of the present invention is as follows: 1. Fully degradable: All components are completely degraded into CO2 and H2O within 6 to 12 months in the body; 2. Degradation synchronization: Through material ratio control, the degradation rate difference of each component is less than 15%; 3. High sensitivity: The sensitivity of the PLA / nHA membrane reaches 0.15 nm / kPa. Compared with Example 5 and Example 3, it can be seen that the sensitivity of the PLA / nHA membrane is 300% higher than that of the pure polylactic acid (PLA) membrane; 4. Optical performance: transmittance>92% (wavelength 1550nm), interference fringe contrast>85%; 5. Sensitivity matching: The measured sensitivity reaches 0.1 kPa⁻¹, which is suitable for scenarios such as intracranial pressure monitoring.
[0043] In addition, the degradation products of the entire sensor components are non-toxic, avoiding secondary surgery; and the price of polylactic acid (PLA) raw materials is only about 1 / 5 of traditional materials, greatly reducing production costs.
[0044] Finally, the embodiments listed above are preferred implementation schemes of the present application and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An optical fiber pressure sensor based on polylactic acid, comprising a base (10), a pressure-sensitive membrane (20) and an optical fiber (30), characterized in that: The base (10) is a blend of polylactic acid (PLA) and nanocellulose; The pressure-sensitive film (20) is a blend of polylactic acid (PLA), nanocellulose and hydroxyapatite; The optical fiber (30) comprises a core layer and a cladding layer, wherein the core layer material is high-purity polylactic acid (PLA), and the cladding layer material is a blend of polylactic acid (PLA) and polyhydroxyalkanoate (PHA).
2. The optical fiber pressure sensor based on polylactic acid according to claim 1, characterized in that: In the pressure-sensitive film (20), the mass ratio of polylactic acid (PLA), nanocellulose and hydroxyapatite is (70-88): (8-22): (2-7).
3. The optical fiber pressure sensor based on polylactic acid according to claim 1, characterized in that: In the cladding of the optical fiber (30), the mass ratio of polylactic acid (PLA) to polyhydroxyalkanoate (PHA) is (80-95): (5-20).
4. The optical fiber pressure sensor based on polylactic acid according to claim 1, characterized in that: A concave cavity is provided on the base (10), and a pressure-sensitive film (20) is covered at the opening of the concave cavity to form an FP cavity. Reflective films (40) are correspondingly provided at the two end faces of the FP cavity, and the reflective films (40) are multilayer polylactic acid (PLA) / polycaprolactone (PCL) films.
5. The optical fiber pressure sensor based on polylactic acid according to claim 4, characterized in that: The multilayer polylactic acid (PLA) layer and polycaprolactone (PCL) layer are arranged alternately, and the layer directly in contact with the end surface of the FP cavity is the polylactic acid (PLA) layer.
6. The optical fiber pressure sensor based on polylactic acid according to claim 4, characterized in that: The reflective film (40) has 5 to 10 layers in total, and a thickness of 0.5 to 1.5 μm.
7. The optical fiber pressure sensor based on polylactic acid according to claim 4, characterized in that: The base (10) comprises a first substrate (11) and a second substrate (12); a first through hole (111) is provided on the first substrate (11); the first through hole (111), the surface of the second substrate (12), and the surface of the pressure-sensitive membrane (20) together enclose an FP cavity; and a reflective film (40) is provided on the surface of the pressure-sensitive membrane (20) and the surface of the second substrate (12) in the FP cavity.
8. The optical fiber pressure sensor based on polylactic acid according to claim 7, characterized in that: An optical fiber sleeve (50) is provided on the second substrate (12); the inner cavity of the optical fiber sleeve (50) and the surface of the second substrate (12) enclose an optical fiber installation portion; the FP cavity and the optical fiber installation portion are coaxially arranged in an axial direction of the optical fiber (30) and spaced apart.
9. The optical fiber pressure sensor based on polylactic acid according to claim 8, characterized in that: The mass ratio of polylactic acid (PLA) and nanocellulose in the base (10) is (95-97): (3-5), and the optical fiber sleeve (50) is pure polylactic acid (PLA).
10. The optical fiber pressure sensor based on polylactic acid according to claim 1, characterized in that: The outer surface of the sensor is sprayed with a PLA protective layer with a thickness of 3 to 6 μm.